Hib vaccination in infants born prematurely. Issue 3 (1st March 2003) - Heath, P T; Booy, R; McVernon, J; Bowen-Morris, J; Griffiths, H; Slack, M P E; Moloney, A C; Ramsay, M E; Moxon, E R
Abstract : Aims: To document the immunogenicity and persistence of antibody to polyribosyl-ribitol phosphate (PRP) as well as the clinical protection against invasive Haemophilus influenzae type b (Hib) disease in premature infants immunised at the routine schedule. Methods: Blood was obtained at 2, 5, 12, and 64 months of age from a cohort of prematurely born infants (≤32 weeks gestation). Anti-PRP antibody concentrations were compared with those of a control cohort of infants born at full term and vaccinated at the same schedule. Hib vaccine failures occurring between October 1992 and October 2000 were reported by paediatricians through an active, prospective, national survey in the UK and Republic of Ireland. The number of prematurely born children with vaccine failure was compared with the corresponding number born at term. Results: Twenty seven prematurely born infants were followed to 5 years of age. Compared with term infants they had a significantly lower geometric mean concentration of anti-PRP antibody and/or a significantly lower proportion above one or both of the conventional protective antibody concentrations (0.15 and 1.0 μg/ml) at all ages. A total of 165 cases of invasive Hib disease were identified over eight years of national surveillance. Eighteen were premature (<37 weeks); approximately 12 would be expected. The relative risk of UK premature infants developing disease compared with term infants was 1.5 (95% CI 0.9 to 2.6). Conclusions: Premature infants develop lower antibody concentrations than term infants following Hib conjugate vaccination. Premature infants may also have an increased risk of clinical vaccine failure, but interpretation is limited by the small number of premature infants developing invasive Hib disease over eight years of national surveillance. Overall, vaccination with Hib conjugate vaccines affords a high level of protection to premature babies.